Interpersonal Communication Strategies in Facing Toxic Dating Relationships: A Study among Communication Science Students at Dehasen University - Zarniati, Devi; Narti, Sri; Dianthi, Martha Heriniazwi (Social Sciences Journal, 2025)
Toxic relationships within romantic contexts are increasingly prevalent among university students, often leading to negative mental health outcomes and distorted interpersonal dynamics. This study investigates how interpersonal communication unfolds in the context of toxic dating relationships among students of the Communication Science Department at Dehasen University. Employing a descriptive qualitative approach, data were collected via in-depth interviews, observation, and documentation from three informants who had experienced excessive control, emotional manipulation, and verbal abuse in their relationships. Findings indicate a breakdown in key interpersonal communication traits—openness was suppressed due to manipulative reactions, empathy was absent as partners lacked mutual understanding, supportiveness took the form of control rather than care, positive attitudes eroded into emotional fatigue, and equality was replaced with domination. The study highlights the need for increased awareness of healthy communication, early recognition of relational toxicity, and institutional support for students at risk. These insights contribute to the broader discourse on student mental health, character education, and interpersonal relationship management in higher education settings.